2021
DOI: 10.3390/life11121333
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Accumulation in Oyster (Crassostrea gigas) Slurry Exposed to Virucidal Cold Atmospheric Plasma Treatment

Abstract: Viral contamination of edible bivalves is a major food safety issue. We studied the virucidal effect of a cold atmospheric plasma (CAP) source on two virologically different surrogate viruses [a double-stranded DNA virus (Equid alphaherpesvirus 1, EHV-1), and a single-stranded RNA virus (Bovine coronavirus, BCoV)] suspended in Dulbecco’s Modified Eagle’s Medium (DMEM). A 15 min exposure effectuated a statistically significant immediate reduction in intact BCoV viruses by 2.8 (ozone-dominated plasma, “low power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 58 publications
1
3
0
Order By: Relevance
“…Some studies have demonstrated that the impacts of NTAPP are significantly selective for cancer cells. The pH of the PTM remained unchanged after NTAPP, which is identical to our results [ 46 , 47 ]. The DMEM has the capacity to maintain the pH and temperature of the PTM [ 48 ].…”
Section: Discussionsupporting
confidence: 92%
“…Some studies have demonstrated that the impacts of NTAPP are significantly selective for cancer cells. The pH of the PTM remained unchanged after NTAPP, which is identical to our results [ 46 , 47 ]. The DMEM has the capacity to maintain the pH and temperature of the PTM [ 48 ].…”
Section: Discussionsupporting
confidence: 92%
“…Considering the novelty of this study, these results and preliminary results can provide a basis for future studies of PASW-oyster depuration efforts (Supplementary Figure S1). However, a few studies have examined cold atmospheric plasma applied directly to oyster meat [45,46]. In the study by Csadek et al (2021), their cold atmospheric plasma treatment inactivated enveloped RNA virus in blended oyster meat slurry.…”
Section: Microbial Inactivation Efficacy Of Pasw10 (1:1) Against Tota...mentioning
confidence: 99%
“…Csadek et al [ 134 ] studied the inactivation of surrogate viruses on an oyster slurry, but employed a DBD instead of a jet-type plasma generator. Plasma was generated from ambient air.…”
Section: Effects Of Cap Treatment Of Aquatic Foods Of Animal Origin: ...mentioning
confidence: 99%
“…Both Choi et al [ 133 ] and Csadek et al [ 134 ] studied oyster tissue and not live oyster, and it was a contamination scenario, not an infection. However, the antiviral effects of CAP exposure can also be expected for live oysters, whereas the significance of the observed nitrogen accumulation in oyster slurry for live animals is not entirely clear.…”
Section: Effects Of Cap Treatment Of Aquatic Foods Of Animal Origin: ...mentioning
confidence: 99%
See 1 more Smart Citation